Tuberculosis 2018
DOI: 10.1183/13993003.congress-2018.pa2756
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of positivity of CBNAAT(cartridge based nucleic acid amplification test) in extra-pulmonary tuberculosis.

Abstract: Original Research Article Introduction: Tuberculosis (TB) remains a key challenge in the face of global public health and inadequate diagnostic assays have hampered our chances to tackle this disease effectively. The Gene X-pert MTB/RIF assay marks an important development in the field of rapid molecular TB diagnostics. This study was done to see the prevalence of gene Xpert MTB/RIF assay and drug resistant tuberculosis in extrapulmonary tuberculosis. Material and methods: The 300 samples of extra-pulmonary tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Another study conducted by Mahesh Gupta et al on prevalence of positivity of CBNAAT in EPTB patients included 300 patients (203 pleural fluid, 58 lymph node aspirate, 18 empyema, 9 ascitic fluid, 9 CSF, 3 pericardial fluid) and diagnosed EPTB on history, clinical and radiological basis. 15 Out of these 28 (13.8%) patients of pleural fluid, 35 (60.3%) patients of lymph node aspirate, 8 (44.4%) patients of empyema, 1 (11.1%) patient of ascitic fluid and none of the CSF and pericardial fluid were CBNAAT positive and out of 72 positive patients 12 (16.7%) were rifampicin resistant. This study concluded that Gene Xpert assay has the potential to significantly improve and escalate the diagnosis from smear negative body fluids in the regions with not only high TB burden but also with overlapping HIV.…”
Section: Discussionmentioning
confidence: 93%
“…Another study conducted by Mahesh Gupta et al on prevalence of positivity of CBNAAT in EPTB patients included 300 patients (203 pleural fluid, 58 lymph node aspirate, 18 empyema, 9 ascitic fluid, 9 CSF, 3 pericardial fluid) and diagnosed EPTB on history, clinical and radiological basis. 15 Out of these 28 (13.8%) patients of pleural fluid, 35 (60.3%) patients of lymph node aspirate, 8 (44.4%) patients of empyema, 1 (11.1%) patient of ascitic fluid and none of the CSF and pericardial fluid were CBNAAT positive and out of 72 positive patients 12 (16.7%) were rifampicin resistant. This study concluded that Gene Xpert assay has the potential to significantly improve and escalate the diagnosis from smear negative body fluids in the regions with not only high TB burden but also with overlapping HIV.…”
Section: Discussionmentioning
confidence: 93%